Pendampingan Praktik Mengajar Calon Guru: Meningkatkan Kompetensi Pedagogik dan Pemahaman Konsep Matematika - Saftari, Maya; Yulianti, Yulianti (Universitas Pahlawan Tuanku Tambusai, 2025)
Teaching practice assistance activities aim to develop pedagogical competence and conceptual understanding of prospective teachers for mathematics subjects so that they are ready to face challenges in an effective learning process. Through an approach that involves micro-teaching, lesson planning, and the use of technology and interactive learning media, prospective teachers are guided to understand and master relevant and adaptive teaching techniques. This method includes classroom simulations, preparation of teaching materials, as well as evaluation and self-reflection practices, which are expected to improve skills in delivering material, managing the class, and adapting learning according to student needs. This mentoring activity was carried out for 2 days on 10 and 11 May 2024. With 2 ISB Atma Luhur lecturers, as resource persons (companions). Participants consisted of 28 prospective teachers who came from various regions in Central Bangka district. The expected result of this mentoring is to increase the ability of prospective teachers to apply active and collaborative teaching strategies, as well as strengthening conceptual understanding in mathematics. It is hoped that this mentoring will be able to equip prospective teachers with the skills and confidence needed to become professional educators who are responsive to educational needs in the modern era.